Getting Started with GEO, CouchDB, and Node.js - Thompson, Mick (O'Reilly Media, 2011)
Today's mobile devices have GPS and standard APIs to give you access to coordinates—but what can you do with that data? With this concise book, application developers learn how to work with location data quickly and easily, using Node.js, CouchDB, and other open source tools and libraries.